Single attosecond pulse and xuv supercontinuum in the high-order harmonic plateau - Chang, Zenghu (My University, 2004)
It is proposed that single attosecond pulses be generated by gating high-order harmonic emission with fields whose ellipticity varies rapidly with time. The laser pulse with a time-dependent ellipticity is created from two 5−fs laser pulses centered at 750nm and separated by 5fs. One of the laser pulses is left-circularly polarized and the other is right-circularly polarized. Numerical simulations show that when neon atoms are driven by such laser pulses, the generated high-order harmonic spectrum in the 25th to the 85th orders are a supercontinuum that corresponds to single attosecond pulses. A simple analytical expression is derived for estimating the high-harmonic radiation time.